SYMPTOMS OF POST-STROKE DEPRESSION - D. Komsiyska (Trakia Journal of Sciences)
The purpose of this manuscript is to present our research on post-stroke depression and compare them to previous observations. Depression is a very common among disorders found in stroke patients, thus there is а high necessity in its research. We have used a contingent of 93 patients in the acute phase after stroke, which were treated at the Neurological Clinic to the University Hospital "Prof. Dr. Stoyan Kirkovich" in Stara Zagora for the period 2015 – 2016. We tested them with The Hamilton Depression Rating Scale (HAM-D-17) and analyzed the results with Statistica, version 10 (StatSoft, Inc.). We found high occurrence of depression in stroke patients. We tested for its severity and for its different symptoms in order to compare them to other studies and discover which are most common in post-stroke depression. As a conclusion, we summarize our results that among our contingent there are predominantly mild and moderate depressive disorders with reduced mood, sadness, increased psychic and somatic anxiety, insomnia, somatic complaints and superfluous hypochondriac thoughts.